The Ambulance Location Can Influence Emergency Medical Service Response Time: A Literature Review - Sanjana, I Wayan Edi; Wihastuti, Titin Andri; Muslihah, Nurul (Research Journal of Life Science, 2021)
Factor of the accident was the highest cause of mortality. The mortality or death caused by accident could be avoided through a fast and appropriate first aid. The ambulance was a component of EMS that must reach the incident location in a quick time. This research was aimed to identify the effects of ambulance station location and ambulance response time.  In the literature review, four databases were used as EBSCOhost, Proquest, Science Direct, and SpringerLink and through access help from Brawijaya University library. PRISMA method was exerted in this research to select the articles and choose as many as 15 research articles that fulfill inclusion criteria. The response time of EMS was very influential for patient care and safety. The standby ambulance location can affect the officer's response time. The determination of the ambulance location for the EMS service provider was very significant to offer an optimal service.